2021
DOI: 10.1371/journal.pone.0256828
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, characteristics, behavioural models and behaviour change strategies, of non-workplace interventions specifically targeting sedentary behaviour; a systematic review and meta-analysis of randomised control trials in healthy ambulatory adults

Abstract: Background Sedentary behaviour (SB) research has grown exponentially but efficacy for interventions to reduce sedentary behaviour is often contaminated by interventions primarily or co-targeting other behaviours and outcomes. The primary aim of this research therefore, was to systematically review the efficacy of interventions specifically targeting sedentary behaviour reduction, as a sole primary outcome, from randomised control trials in healthy ambulatory adults. This research also sought to identify the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
(257 reference statements)
0
10
0
Order By: Relevance
“…Despite these recommendations and recent SB research, pooled evidence from reviews on the effectiveness of interventions to reduce SB is limited by heterogeneity of outcomes [ 11 , 12 ]. This field of research spans many disciplines, interventions and populations, and the heterogeneity of outcomes, ‘what to measure and report’, is a fundamental stumbling block to the accumulation and aggregation of evidence [ 13 , 14 , 15 ]. Rapid growth in both laboratory and personal activity sensing devices now provide an abundance of data for potential analysis [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these recommendations and recent SB research, pooled evidence from reviews on the effectiveness of interventions to reduce SB is limited by heterogeneity of outcomes [ 11 , 12 ]. This field of research spans many disciplines, interventions and populations, and the heterogeneity of outcomes, ‘what to measure and report’, is a fundamental stumbling block to the accumulation and aggregation of evidence [ 13 , 14 , 15 ]. Rapid growth in both laboratory and personal activity sensing devices now provide an abundance of data for potential analysis [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of a standardised COS for reporting SB outcomes will facilitate comparability and meta-analyses of data from intervention trials in this complex research field. This critical action research project was identified following a recent systematic literature review, led by members of the research team, of randomised controlled trials of interventions designed specifically to change SB across all domains of living, unpublished and published [ 15 ]. Consistent with a prior review [ 34 ], heterogeneity in measuring and reporting SB in interventions was a limitation noted in the review, preventing inclusion of all of the study data in meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…To this respect, an individual level framework, such as microsimulation [ 23 ], can be more suitable, provided relevant data are available. Lack of long-term follow-up data is a common hurdle of public health evaluations, not least the information regarding the sustainability of intervention effects [ 5 ]. Nevertheless, this does not justify the use of implausible assumptions and lack of robustness checks.…”
Section: Discussionmentioning
confidence: 99%
“…In these evaluations, however, is estimating long term intervention effects (e.g., changes in physical activity (PA) habits) is often a challenge [ 4 ]. Effectiveness evidence tends to be short-term [ 5 ], whilst most health benefits accrue over the long term [ 6 ]. Acknowledging this issue, the National Institute for Health and Care Excellence (NICE) recommends the application of extrapolation methods and careful consideration in defining model assumptions that ought to be plausible and related uncertainties that need to be fully explored and systematically addressed [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of energy expenditure (EE) is fundamental to determine the level of physical activity of a person. The current society we live in has eminently sedentary behaviour, which can produce serious problems, and along with other unhealthy lifestyle habits, means a change in lifestyle is necessary [ 1 , 2 ]. Likewise, the use of behaviour modification techniques alone can produce an increase in physical activity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%